2022
DOI: 10.3389/fmicb.2022.859990
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Enterococcus hirae From Beef Cattle Feedlots and Associated Environmental Continuum

Abstract: Enterococci are commensal bacteria of the gastrointestinal tract of humans, animals, and insects. They are also found in soil, water, and plant ecosystems. The presence of enterococci in human, animal, and environmental settings makes these bacteria ideal candidates to study antimicrobial resistance in the One-Health continuum. This study focused on Enterococcus hirae isolates (n = 4,601) predominantly isolated from beef production systems including bovine feces (n = 4,117, 89.5%), catch-basin water (n = 306, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 117 publications
1
7
0
Order By: Relevance
“…The probiotic potential of E. hirae observed in this work was in line with the finding of Arokiyaraj et al (2014), Kamni and Ramesh (2020), de Castro Santos Melo et al (2021), and Rajput et al (2022. Its antibiotic susceptibility contradicts the findings of Zaidi et al (2022) who reported that antimicrobial susceptibility profiling of E. hirae isolates originating from beef production systems showed high resistance to tetracycline (65%) and erythromycin (57%) with 50.4% isolates harboring multidrug resistance while it was in conformity with the work of Kamni and Ramesh (2020) who isolated E hirae from indigenous raw goat milk and reported that it was susceptible to amikacin, carbenicillin kanamycin, ciprofloxacin, co-trimazine, nitrofurantoin, streptomycin, and tetracycline.…”
Section: Discussionsupporting
confidence: 88%
“…The probiotic potential of E. hirae observed in this work was in line with the finding of Arokiyaraj et al (2014), Kamni and Ramesh (2020), de Castro Santos Melo et al (2021), and Rajput et al (2022. Its antibiotic susceptibility contradicts the findings of Zaidi et al (2022) who reported that antimicrobial susceptibility profiling of E. hirae isolates originating from beef production systems showed high resistance to tetracycline (65%) and erythromycin (57%) with 50.4% isolates harboring multidrug resistance while it was in conformity with the work of Kamni and Ramesh (2020) who isolated E hirae from indigenous raw goat milk and reported that it was susceptible to amikacin, carbenicillin kanamycin, ciprofloxacin, co-trimazine, nitrofurantoin, streptomycin, and tetracycline.…”
Section: Discussionsupporting
confidence: 88%
“…1 and Table 3 , 4 , 5 and S1). Studies on E. faecium, E. faecalis , and E. hirae have shown that, even at the species level, virulence-associated elements, such as biofilm formation and cell adhesion, and carbohydrate metabolism are highly niche-dependent (Zaidi et al 2022 ). Additionally, food-related enterococcal strains tend to have multiple copies of those genes required to use specific carbohydrates, such as lactose, and of certain proteolytic genes due to the selective pressure of the medium (Olvera-García et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…faecalis are more prevalent in human-associated environments, E . hirae is a common coloniser of animal species, especially cattle, and can be easily isolated from cattle manure and water samples from feeding basins [ 67 , 68 ]. E .…”
Section: Discussionmentioning
confidence: 99%
“…are rarely implicated as pathogens, consumption of these bacteria can lead to their establishment in the gastrointestinal tract [66]. While E. faecium and E. faecalis are more prevalent in humanassociated environments, E. hirae is a common coloniser of animal species, especially cattle, and can be easily isolated from cattle manure and water samples from feeding basins [67,68]. E. hirae was the predominant species recovered from cattle production systems including both bovine feces (92%), and feedlot catch basins (60%), it was not isolated in any of the 1849 human clinical samples it was sampled [68].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation